Village Youtuber in the Perspective of Glocalization - Permatasari, Delmarrich Billga Ayu (Semantik: Journal of Social, Media, Communication, and Journalism, 2024)
In the landscape of evolving social media platforms, YouTube stands out as a dynamic force, continuing to expand its reach globally. With a user base of 2 billion monthly visitors, YouTube ranks second among social media apps, showcasing its unparalleled potential for content creators. YouTube as a globalized platform does not always produce global content. In Indonesia, YouTube content produced by YouTubers with local themes has been able to gain tremendous exposure. By using Roland Robertson's theory of glocalization, this study aims explores the phenomenon of YouTube as a product of globalization, examining its role in shaping local identities within a global framework. Through an analysis of YouTube content from Dimas Zaenal Universe (DZU), a group of content creators from rural Indonesia, this research delves into the intricate dynamics of glocalization. By focusing on the themes of locality, language, and cultural adaptation, the study aims to understand how DZU's YouTube channel navigates the intersection between global platform dynamics and local identity formation. The findings of this research simplicity and naturalness with a local indegeneous spirit characterize the existence of YouTuber Kampung in fighting in the global platform arena in Indonesia. This study illustrates the power of glocalization, where the local and global intersect to create a new, hybrid form of digital presence.